Method for simultaneously improving strength and plasticity of NiCoCrFeAlW eutectic high-entropy alloy

Through directional solidification technology, the solidification process of NiCoCrFeAlW eutectic high-entropy alloy is regulated, and the strength and plastic trade-offs of traditional alloys are solved, and the mechanical properties of the alloys are improved, which is suitable for applications in multiple fields.

CN119320886APending Publication Date: 2025-01-17LANZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411442325.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Traditional eutectic high-entropy alloys have trade-offs between strength and plasticity. The existing processing methods are complex and difficult to mass-produce in industrial-scale production, and it is difficult to simultaneously improve their strength and plasticity.

Method used

Directional solidification technology is adopted to accurately control the melting and solidification process, and regulate the solidification process of NiCoCrFeAlW eutectic high-entropy alloy, eliminate lateral grain boundaries, reduce dendritic spacing, reduce solidification defects, and improve the tensile strength and elongation of the alloy.

Benefits of technology

The mechanical properties of NiCoCrFeAlW eutectic high-entropy alloy have been significantly improved, and the tensile strength and elongation are improved. They are suitable for aerospace, nuclear energy industry and high-performance structural materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320886A_ABST
    Figure CN119320886A_ABST
Patent Text Reader

Abstract

The invention discloses a method for simultaneously improving strength and plasticity of NiCoCrFeAlW eutectic high-entropy alloy, which comprises the following steps: weighing and proportioning Ni, Co, Cr, Fe, Al and W metal elementary substances with the purity exceeding 99.5% as raw materials according to a molar ratio, smelting in an electric arc smelting furnace, repeating the smelting process for 2-8 times in order to ensure the uniformity of components, and naturally cooling until solidification, thereby obtaining the NiCoCrFeAlW eutectic high-entropy alloy. And then linear cutting is carried out to obtain a rod-shaped as-cast alloy sample, the rod-shaped as-cast alloy sample is placed in a directional solidification furnace, and heating and heat preservation treatment is carried out on the rod-shaped as-cast alloy sample in the argon atmosphere. According to the preparation method disclosed by the invention, the NiCoCrFeAlW eutectic high-entropy alloy with excellent mechanical properties is successfully prepared by accurately controlling smelting and directional solidification processes. Compared with a traditional eutectic high-entropy alloy, the alloy obtained through the technology shows higher tensile strength and ductility. Due to the remarkable improvement and improvement of the mechanical properties, the alloy has greater application potential in the fields of aerospace, nuclear energy industry, high-performance structural materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, in particular to a method for simultaneously improving the strength and plasticity of a NiCoCrFeAlW eutectic high entropy alloy. Background Art

[0002] Eutectic high entropy alloy is a multi-principal alloy. Since it was first proposed in 2014, it has attracted widespread attention due to its excellent mechanical properties, casting properties and corrosion resistance. This type of alloy combines the advantages of eutectic alloys and high entropy alloys and has broader application prospects. However, traditional eutectic high entropy alloys often have a trade-off between strength and plasticity, which limits their further development in engineering applications. Therefore, some processes are usually required to improve their performance.

[0003] Directional solidification technology is a method of inducing the growth of solidified structures in a specific direction by controlling the direction of heat flow during the solidification process of the alloy. This technology has been widely used in the preparation of materials such as titanium aluminum alloys to improve their mechanical properties. Directional solidification technology allows precise control of the solidification process, including the crystal growth direction, solidification rate and cooling rate, thereby controlling its microstructure. In addition, directional solidification technology can also directionalize the grains, without grain boundaries perpendicular to the stress direction, thereby greatly reducing the thermal stress caused by uneven temperature and improving the creep rupture life and thermal fatigue strength of the material. The most classic AlCoCrFeNi 2.1 Eutectic high entropy alloys have obtained better strength and plasticity through directional solidification technology (P.Peng, SYLi, WQChen, YLXu, XDZhang, ZKMa, JTWang, Phase selection and mechanical properties of directionally solidified AlCoCrFeNi 2.1 eutectic high-entropy alloy, Journal of Alloys and Compounds, 898(2022)162907).

[0004] NiCoCrFeAlW eutectic high entropy alloy was first designed by Wu Qingfeng and others from Northwestern Polytechnical University, and has relatively good strength and ductility (QFWu, ZJWang, T.Zheng, D.Chen, ZSYang, Junjie Li, Ji-jung Kai, Jincheng Wang, A casting eutectic high entropy alloy with superior strength-ductility combination, Materials Letters, 253 (2019) 268-271). The eutectic high entropy alloy is composed of B2 phase and FCC phase, with a semi-coherent interface. At present, the research on this eutectic high-entropy alloy is mainly focused on how to improve its mechanical properties. Wang Zhijun's team added an appropriate amount of boron at high temperature, first performed an initial solution treatment for 2 hours, then used phase selective recrystallization to heat treat the material after solution, and finally performed 30% cold rolling and aging treatment at 700℃ for 3 hours. The FCC grain boundary and FCC / B2 phase boundary can be strengthened (YHJia, ZJWang, QFWu, YFWei, XYBai, LXLiu, JYWang, XMLiu, L.Wang, F.He, JJLi, JCWang, Boronmicroalloying for high-temperature eutectic high-entropy alloys, ActaMaterialia, 262(2024)119427) to obtain better strength and plasticity. Wu Qingfeng et al. strengthened the eutectic high entropy alloy by phase selective recrystallization, mainly through cyclic cold rolling and annealing treatment (QFWu, F.He, J.Li, et al. Phase-selective recrystallization makes eutectic high-entropy alloys ultra-ductile. Nature Communications 13, (2022) 4697). In the current treatment methods, phase selective recrystallization is required, which requires precise control of processing parameters such as deformation and annealing temperature to obtain the desired microstructure. This precise control will increase the complexity and cost of the manufacturing process. To achieve the ideal phase selective recrystallization microstructure, it is necessary to finely control the microstructure of the material, which is very difficult in actual operation, especially in industrial-scale production. Therefore, the treatment methods reported in the above literature can only exist in laboratory design, which is extremely challenging in actual industrial production and difficult to mass produce.

[0005] Although eutectic high entropy alloys have made certain progress in composition design, organization regulation and material preparation, how to effectively combine directional solidification technology to further improve the performance of the alloy, especially to maintain greater plasticity while improving strength, is still a challenge. The present invention aims to control the solidification process of NiCoCrFeAlW eutectic high entropy alloy through directional solidification technology, so as to achieve organization growth control, so as to simultaneously improve the strength and plasticity of the alloy and overcome the limitations of the prior art. Directional solidification technology can make the grains oriented, and there is no grain boundary perpendicular to the stress direction, thereby greatly reducing the thermal stress caused by uneven temperature and improving the creep rupture life and thermal fatigue strength of the material. This method does not have the complexity of the above-mentioned phase selective recrystallization, is more practical, and can achieve mass production.

[0006] In summary, the present invention provides a method for improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy during sample solidification by directional solidification technology, and the method is expected to play a huge application potential in the field of engineering applications. Through the technical solution of the present invention, the comprehensive mechanical properties of eutectic high entropy alloy can be significantly improved, which provides the possibility for its application in more fields. Summary of the invention

[0007] The purpose of the present invention is to provide a method for simultaneously improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloys, and successfully prepare NiCoCrFeAlW eutectic high entropy alloys with excellent mechanical properties by precisely controlling the melting and directional solidification processes. Compared with traditional eutectic high entropy alloys, the alloys obtained by the technology of the present invention exhibit higher tensile strength and elongation. The significant improvement and improvement of these mechanical properties make the alloys have greater application potential in the fields of aerospace, nuclear energy industry and high-performance structural materials.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The directional solidification technology of the present invention can eliminate the transverse grain boundaries in the alloy, effectively reduce the dendrite spacing and reduce the probability of various solidification defects, so that the alloy has more excellent mechanical properties; the reduction of dendrite structure and lamellar spacing and the increase of phase boundaries in the directionally solidified NiCoCrFeAlW eutectic high entropy alloy improve the mechanical properties of the alloy such as tensile strength;

[0010] A method for simultaneously improving the strength and plasticity of a NiCoCrFeAlW eutectic high entropy alloy proposed in the present invention comprises the following steps:

[0011] (1) Using Ni, Co, Cr, Fe, Al, and W metal single substances with a purity of more than 99.5% as raw materials, weighing and proportioning them according to the molar ratio, placing them in an arc melting furnace for melting, repeating the melting process 2-8 times to ensure the uniformity of the composition, cooling naturally until solidification, and then performing wire cutting to obtain a rod-shaped cast alloy sample;

[0012] (2) placing the rod-shaped cast alloy sample described in step (1) in a directional solidification furnace, and heating and heat-insulating it in an argon atmosphere;

[0013] (3) After the heat preservation treatment in step (2) is completed, the cast alloy sample is pulled and quenched to obtain a directionally solidified alloy.

[0014] Preferably, the heating and heat preservation treatment in step (2) is: heating the cast alloy sample from room temperature to 1540-1800°C at a rate of 20-30°C / min, and keeping it warm for 20-50min.

[0015] Preferably, the pulling rate of the directional solidification in step (3) is 10-200 μm / s, and the pulling distance is 50-70 mm.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention successfully prepares NiCoCrFeAlW eutectic high entropy alloy with excellent mechanical properties by precisely controlling the melting and directional solidification processes. Compared with traditional eutectic high entropy alloys, the alloy obtained by the technology of the present invention exhibits higher tensile strength and elongation. The significant improvement and improvement of these mechanical properties make the alloy have greater application potential in the fields of aerospace, nuclear energy industry and high-performance structural materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a diagram showing the room temperature tensile properties of the alloy obtained at different pulling rates;

[0019] Figure 2 Schematic diagram of the specimen dimensions and cutting for the tensile test: (a) Directionally solidified NiCoCrFeAlW specimen; (b) tensile specimen dimensions; (c) schematic diagram of the position where the tensile specimen is cut from the directionally solidified specimen.

[0020] Figure 3 SEM photographs of the stable growth zone morphology of alloy dendrites and lamellar eutectics obtained at different pulling rates: (a) 10μm / s, (b) 20μm / s, (c) 50μm / s, (d) 100μm / s, and (e) 200μm / s.

[0021] Figure 4 This is the EDS image of NiCoCrFeAlW eutectic high entropy alloy;

[0022] Figure 5 are the dark-field TEM images of the as-cast sample, the selected area electron diffraction (SAED) pattern, and the corresponding EDS mappings of the two phases, FCC and B2;

[0023] Figure 6 It is the X-ray diffraction spectra of directionally solidified alloy and cast alloy samples at different pulling rates;

[0024] Figure 7 EBSD images of NiCoCrFeAlW eutectic high entropy alloy: (a) as-cast alloy, (b) 20 μm / s, (c) 100 μm / s, showing the distribution of FCC (green) and B2 (red) phases. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention provides a method for simultaneously improving the strength and plasticity of a NiCoCrFeAlW eutectic high entropy alloy, comprising the following steps:

[0027] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are placed in an arc melting furnace and melted under the protection of high-purity argon. During the first melting, the working current of the melting furnace is gradually increased. After complete melting, the melting is stopped, and the alloy is naturally cooled to solidification and cut to obtain a rod-shaped cast alloy sample.

[0028] Furthermore, the Ni 30 Co 30 Cr 10 Fe 10 Al 18 The W2 eutectic high entropy alloy includes the following components in molar percentages: Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2%.

[0029] Furthermore, in order to ensure the uniformity of the alloy composition, the solidified alloy is completely melted again before the cutting step and then naturally cooled to solidification, and this smelting step is repeated 2-8 times, preferably 5 times, to obtain an alloy ingot; the cutting method is wire cutting, and after cutting, a rod-shaped cast alloy sample with a size of Φ7mm×100mm is obtained.

[0030] (2) placing the as-cast alloy sample in a directional solidification furnace, and heating and heat-insulating the as-cast alloy sample in an argon atmosphere.

[0031] In this step, the heating and heat preservation treatment is specifically: heating the cast alloy sample from room temperature to 1540-1800°C at a rate of 20-30°C / min, and keeping it warm for 20-50min. Preferably, the cast alloy sample is heated from room temperature (25°C) to 1540°C at a heating rate of 25°C / min, and the sample is kept warm after reaching 1540°C, and the holding time is 30min.

[0032] (3) Drawing the alloy sample after the insulation treatment in step (2), and quickly immersing the alloy sample in a coolant for quenching after drawing, to obtain a directionally solidified alloy.

[0033] In this step, the pulling rate is 10-200 μm / s, preferably 50-100 μm / s, for example, 50 μm / s, 70 μm / s, 100 μm / s; the pulling distance is 50-70 mm, for example, 50 mm, 60 mm, 70 mm, etc.

[0034] The directionally solidified alloy obtained by the above method of the present invention is tested for mechanical properties, and the detection method is as follows:

[0035] The directionally solidified alloy was subjected to electrospark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.

[0036] For a certain system of alloys, the growth characteristics of the alloy structure during directional solidification are mainly controlled by the cooling rate. Therefore, the cooling rate can be regulated and optimized to adjust and improve the alloy structure and ultimately achieve effective improvement in the performance of eutectic high-entropy alloys. The regulation and change of cooling rate is mainly based on two key solidification parameters: temperature gradient and pulling rate. High temperature gradient can be achieved by using liquid metal cooling method, while pulling rate is easier to regulate than temperature gradient.

[0037] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0038] Comparative Example 1

[0039] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0040] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0041] (3) The rod-shaped cast alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2 ), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0042] Example 1

[0043] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0044] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0045] (3) The rod-shaped cast alloy sample obtained in step (2) is placed in a directional solidification furnace. In an argon atmosphere, the sample is heated from room temperature (25°C) to 1550°C at a heating rate of 25°C / min. After the sample temperature reaches 1540°C, the sample is subjected to a heat preservation treatment for 30 minutes. After the heat preservation treatment is completed, the alloy sample is pulled at a pulling rate of 10 μm / s and a pulling distance of 60 mm. After the pulling is completed, the sample is quickly immersed in a coolant for quenching to obtain a directional solidification alloy with a pulling rate of 10 μm / s.

[0046] (4) The directionally solidified alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2 ), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0047] Example 2

[0048] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0049] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0050] (3) The rod-shaped cast alloy sample obtained in step (2) is placed in a directional solidification furnace. In an argon atmosphere, the sample is heated from room temperature (25°C) to 1540°C at a heating rate of 25°C / min. After the sample temperature reaches 1540°C, the sample is subjected to a heat preservation treatment for 30 minutes. After the heat preservation treatment is completed, the alloy sample is pulled at a pulling rate of 20 μm / s and a pulling distance of 60 mm. After the pulling is completed, the sample is quickly immersed in a coolant for quenching to obtain a directional solidification alloy with a pulling rate of 20 μm / s.

[0051] (4) The directionally solidified alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0052] Example 3

[0053] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0054] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0055] (3) The rod-shaped cast alloy sample obtained in step (2) is placed in a directional solidification furnace. In an argon atmosphere, the sample is heated from room temperature (25°C) to 1540°C at a heating rate of 25°C / min. After the sample temperature reaches 1540°C, the sample is subjected to a heat preservation treatment for 30 minutes. After the heat preservation treatment is completed, the alloy sample is pulled at a pulling rate of 50 μm / s and a pulling distance of 60 mm. After the pulling is completed, the sample is quickly immersed in a coolant for quenching to obtain a directionally solidified alloy with a pulling rate of 50 μm / s.

[0056] (4) The directionally solidified alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2 ), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0057] Example 4

[0058] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0059] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0060] (3) placing the rod-shaped cast alloy sample obtained in step (2) in a directional solidification furnace, and heating the sample from room temperature (25°C) to 1540°C at a heating rate of 25°C / min under an argon atmosphere. After the sample temperature reaches 1540°C, the sample is subjected to a heat preservation treatment for 30 minutes. After the heat preservation treatment is completed, the alloy sample is pulled at a pulling rate of 100 μm / s and a pulling distance of 60 mm. After the pulling is completed, the sample is quickly immersed in a coolant for quenching to obtain a directionally solidified alloy with a pulling rate of 100 μm / s.

[0061] (4) The directionally solidified alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2 ), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0062] Example 5

[0063] (1) High-purity Ni, Co, Cr, Fe, Al, and W metal elements with a purity exceeding 99.5% are weighed and proportioned according to the molar percentage ratio of Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18%, and W 2% to obtain an alloy raw material.

[0064] (2) placing the alloy raw material obtained in step (1) in an arc melting furnace, and melting the alloy under the protection of high-purity argon gas. During the first melting, the operating current of the melting furnace is gradually increased until the particles are completely melted, and then the melting is stopped. The alloy is naturally cooled to solidify. To ensure the uniformity of the alloy composition, the alloy is melted again and then naturally cooled. This process is repeated 5 times to obtain an alloy ingot. The alloy ingot is cut by wire cutting to obtain a rod-shaped cast alloy sample with a size of Φ7 mm×100 mm.

[0065] (3) The rod-shaped cast alloy sample obtained in step (2) is placed in a directional solidification furnace. In an argon atmosphere, the sample is heated from room temperature (25°C) to 1540°C at a heating rate of 25°C / min. After the sample temperature reaches 1540°C, the sample is subjected to a heat preservation treatment for 30 minutes. After the heat preservation treatment is completed, the alloy sample is pulled at a pulling rate of 200 μm / s and a pulling distance of 60 mm. After the pulling is completed, the sample is quickly immersed in a coolant for quenching to obtain a directional solidification alloy with a pulling rate of 200 μm / s.

[0066] (4) The directionally solidified alloy obtained in step (3) is subjected to electric spark cutting to obtain a tensile specimen (such as Figure 2 ), the specimens were subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used. The maximum load was 100 kN and the tensile rate was 0.5 mm / min (the corresponding tensile test engineering stress-strain curve is shown in Figure 1 shown).

[0067] Table 1 Tensile mechanical properties of comparative examples and example alloys

[0068]

[0069] Directed solidification Ni obtained at different pulling rates of the present invention 30 Co 30 Cr 10 Fe 10 Al 18 The room temperature tensile engineering stress-strain curve of W2 eutectic high entropy alloy is shown in Figure 1 As shown, the mechanical properties data are shown in Table 1. It can be seen that as the pulling rate increases from 10μm / s to 50μm / s, the yield strength and fracture strength of the alloy increase significantly, and the elongation of the alloy also increases accordingly with the increase of the pulling rate. The mechanical properties of the alloy reach the best at 50μm / s; then as the pulling rate further increases to 200μm / s, the yield strength and fracture strength of the alloy decrease. Comprehensive comparison shows that when the pulling rate is 50μm / s, the directionally solidified Ni 30 Co 30 Cr10 Fe 10 Al 18 The W2 eutectic high entropy alloy has the best comprehensive mechanical properties.

[0070] The reasons for the change of mechanical properties are Figure 3 The change of alloy structure with pulling rate is explained. Figure 3 It can be seen that when the pulling rate is not more than 50μm / s, the dendrite structure is refined with the increase of the pulling rate, which reduces the probability of crack initiation and expansion, which is beneficial to the improvement of the alloy strength; microscopically, with the increase of the pulling rate, the interface area between the B2 phase and the FCC phase increases, which can more effectively hinder the dislocation movement, thereby improving the strength of the alloy. The refinement of the dendrite structure and the increase of the phase interface are also beneficial to the improvement of the alloy toughness. However, as the pulling rate further increases to 100μm / s, the interdendritic lamellar organization area becomes smaller, which in turn reduces the strength of the alloy. Therefore, the tensile strength of the sample with a pulling rate of 50μm / s is the best. Figure 4 This is an EDS image of a cast high entropy alloy sample. The elemental analysis results show that Ni and Al are concentrated in the huge dendrite area, while in the eutectic area, the dark gray phase is high concentration of Ni and Al, and the light gray phase is Co, Cr, Fe and W. Figure 5 From the dark field TEM images, selected area electron diffraction (SAED) patterns, and EDS mapping of the two phases, it can be concluded that the phase structure composed of Ni and Al is the B2 phase, and the phase structure composed of Co, Cr, Fe, and W is the FCC phase. Figure 6 It can be seen that the phase composition content of the directionally solidified alloy grown at different pulling rates is different. Therefore, adjusting the pulling rate affects the phase composition, thereby affecting its mechanical properties. Compared with the cast alloy, the dendrite arrangement of the directionally solidified alloy is more regular (such as Figure 7 ), through the preparation method of directional solidification, the arrangement of them in the axial direction is more regular, so that the mechanical properties of the alloy are better.

[0071] In Example 3, when the pulling rate is 50 μm / s, the room temperature tensile performance of the obtained directionally solidified NiCoCrFeAlW eutectic high entropy alloy reaches an optimal tensile strength of 1286 MPa and an elongation of 21.4%. These data show that the alloy of the present invention is superior to the existing eutectic high entropy alloy in key mechanical performance indicators. Directional solidification technology can well improve the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy.

[0072] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0073] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for simultaneously improving the strength and plasticity of a NiCoCrFeAlW eutectic high entropy alloy, characterized in that: The following steps are involved: S1. Using Ni, Co, Cr, Fe, Al, and W metal single substances as raw materials, weighing and proportioning them according to the molar ratio, placing them in an arc melting furnace for melting, repeating the melting process 2-8 times to ensure the uniformity of the components, naturally cooling to solidification, and then performing wire cutting to obtain a rod-shaped cast alloy sample; S2, placing the rod-shaped cast alloy sample in step S1 in a directional solidification furnace, and heating and heat-insulating it in an argon atmosphere; S3. After the heat preservation treatment in step S2 is completed, the as-cast alloy sample is pulled and quenched to obtain a directionally solidified alloy.

2. The method for simultaneously improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy according to claim 1, characterized in that: In the step S1, the purity of the metal elements Ni, Co, Cr, Fe, Al and W all exceeds 99.5%.

3. The method for simultaneously improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy according to claim 1, characterized in that: In step S2, the heating and heat preservation treatment is as follows: heating the as-cast alloy sample from room temperature to 1540-1800° C. at a rate of 20-30° C. / min, and keeping the temperature for 20-50 min.

4. The method for simultaneously improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy according to claim 1, characterized in that: In the step S3, the pulling rate of directional solidification is 10-200 μm / s, and the pulling distance is 50-70 mm.

5. The method for simultaneously improving the strength and plasticity of NiCoCrFeAlW eutectic high entropy alloy according to claim 1, characterized in that: The molar percentage ratio of the metal elements Ni, Co, Cr, Fe, Al and W is: Ni 30%, Co 30%, Cr 10%, Fe 10%, Al 18% and W 2%.

Citation Information

Cited By

  • Eutectic high-entropy alloy with good strength and plasticity and preparation method of eutectic high-entropy alloy

    CN121294903A